Encuentro - Yolen, Jane.; Shannon, David, 1959-; Ada, Alma Flor. (San Diego : Harcourt Brace & Co., 1996)
A Taino Indian boy on the island of San Salvador recounts the landing of Columbus and his men in 1492.
"Libros viajeros."
Keywords: Columbus, Christopher -- Fiction; Columbus, Christopher -- Novela; Taino Indians -- Fiction; Tainos -- Novela; Indians of the West Indies -- Fiction; Indios de las Antillas -- Novela; Spanish language materials